2022
DOI: 10.1038/s41598-022-18931-0
|View full text |Cite
|
Sign up to set email alerts
|

New treatment strategy for chronic low back pain with alpha wave neurofeedback

Abstract: The lifetime prevalence of low back pain is 83%. Since there is a lack of evidence for therapeutic effect by cognitive behavioral therapy (CBT) or physical therapy (PT), it is necessary to develop objective physiological indexes and effective treatments. We conducted a prospective longitudinal study to evaluate the treatment effects of CBT, PT, and neurofeedback training (NFT) during alpha wave NFT. The early-chronic cases within 1 year and late-chronic cases over 1 year after the diagnosis of chronic low back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Previous EEG-NF studies, including case reports/non-randomised/open-label studies, targeted training higher frequency bands at specific electrode levels in individuals with chronic pain conditions 15 17 . Studies investigating the effect of EEG-NF training on CLBP outcomes are lacking; only two pilot studies have been reported to date 18 , 19 targeting the alpha frequency at the sensor level rather than training specific brain regions at the source level. Higher frequency bands are believed to be nested on the infraslow frequency (ISF) bands (0.0–0.1 Hz) 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous EEG-NF studies, including case reports/non-randomised/open-label studies, targeted training higher frequency bands at specific electrode levels in individuals with chronic pain conditions 15 17 . Studies investigating the effect of EEG-NF training on CLBP outcomes are lacking; only two pilot studies have been reported to date 18 , 19 targeting the alpha frequency at the sensor level rather than training specific brain regions at the source level. Higher frequency bands are believed to be nested on the infraslow frequency (ISF) bands (0.0–0.1 Hz) 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The types оf neurofeedback used іn the studies considered include electroencephalographic (EEG) neurofeedback, infra-low frequency (ILF) neurofeedback, volitional limbic neuromodulation, SMR-based neurofeedback, alpha-wave neurofeedback, and rt-fMRI neurofeedback ( Jensen et al, 2013 ; Guan et al, 2015 ; Hassan et al, 2015 ; Goldway et al, 2019 ; Terrasa et al, 2020 ; Arina et al, 2022 ; Demarest et al, 2024 ). These studies have shown promising results, with notable reductions іn non-pain-related symptoms and pain relief іn patients with chronic pain ( Terrasa et al, 2020 ; Barbosa-Torres and Delgado, 2021 ; Shimizu et al, 2022 ) and with a significant impact оn pain intensity іn the immediate period ( Hesam-Shariati et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neurofeedback has gained attention as a potential treatment for chronic low back pain. Shimizu et al (2022) conducted an intervention study combining alpha-wave neurofeedback training with conventional treatments for chronic low back pain, reporting a clinically meaningful effect оn pain intensity іn the short term. Roy et al (2020) emphasized the potential оf neurofeedback іn pain management, highlighting the association оf neurophysiological abnormalities with pain and the rationale for treatments targeting these factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations